The Effect of Extrinsic Motivation, Interpersonal Trust, and Organizational Commitment in Improving Employee Performance - Rahmat Gunawan; Haerofiatna; Didit Haryadi (Institute of Computer Science (IOCS), 2022)
Some problems must be corrected, namely a decrease in employee performance caused by employees not getting motivated, the level of employee trust decreases, and the low level of commitment possessed by employees. This research examines and analyzes the effect of extrinsic motivation, interpersonal trust, and organizational commitment on employee performance. Quantitative studies are used to get practical answers. The object of this research was the Serpong Regional Income Management employees of the Regional Revenue Agency of Banten Province, with 64 respondents who had been used. Questionnaire answers were measured using an interval scale of 1 – 10. Data were analyzed using the SmartPLS Version 4.0 software. The results of this study state that 1). Extrinsic motivation has a positive and significant effect on employee performance. 2). Interpersonal trust positively and significantly affects employee performance. 3). Organizational commitment positively and significantly affects employee performance.